Association of fibromyalgia with altered skeletal muscle characteristics which may contribute to postexertional fatigue in postmenopausal women1. Issue 2 (28th January 2013) - Srikuea, Ratchakrit; Symons, T. Brock; Long, Douglas E.; Lee, Jonah D.; Shang, Yu; Chomentowski, Peter J.; Yu, Guoqiang; Crofford, Leslie J.; Peterson, Charlotte A.
Abstract Objective To identify muscle physiologic properties that may contribute to postexertional fatigue and malaise in women with fibromyalgia (FM). Methods Healthy postmenopausal women with (n = 11) and without (n = 11) FM, ages 51–70 years, participated in this study. Physical characteristics and responses to self‐reported questionnaires were evaluated. Strength loss and tissue oxygenation in response to a fatiguing exercise protocol were used to quantify fatigability and the local muscle hemodynamic profile. Muscle biopsies were performed to assess between‐group differences in baseline muscle properties using histochemical, immunohistochemical, and electron microscopic analyses. Results There was no significant difference between healthy controls and FM patients in muscle fatigue in response to exercise. However, self‐reported fatigue and pain were correlated with prolonged loss of strength following 12 minutes of recovery in patients with FM. Although there was no difference in percent succinate dehydrogenase (SDH)–positive (type I) and SDH‐negative (type II) fibers or in mean fiber cross‐sectional area between groups, FM patients exhibited greater variability in fiber size and altered fiber size distribution. In healthy controls only, fatigue resistance was strongly correlated with the size of SDH‐positive fibers and hemoglobin oxygenation. In contrast, FM patients with the highest percentage of SDH‐positive fibers recovered strength most effectively, and this was correlated with capillary density. However, overall, capillary density was lower in the FM group. Conclusion Peripheral mechanisms, i.e., altered muscle fiber size distribution and decreased capillary density, may contribute to postexertional fatigue in FM. Understanding of these defects in fibromyalgic muscle may provide valuable insight with regard to treatment.